Effect of process temperature and percentage of rock sugar on the functional group intensity of red ginger extract - Amalia Cantika Asyafa; Dessy Agustina Sari (Institute of Computer Science (IOCS), 2023)
Red ginger has various health benefits that can be consumed in various ways, one of which is an instant powder drink, which is practical and extends the shelf life of the product. The processing process involves cooking at high temperatures with the help of sugar as a crystallization agent. This research aims to understand the effects of temperature and sugar concentration on red ginger extract. The variables used are temperatures of 80 and 90°C and rock sugar concentrations of 60% and 100%. Product evaluation was carried out using Fourier Transform Infrared Spectroscopy (FT-IR) to identify product functional groups. The research results showed that there were differences in functional group content between solid and liquid samples, both fresh raw materials and dregs. In the solid sample, seven functional groups were identified: N-H, C-H, C-H bending, C-N, C=C, C-C, and C-O. Meanwhile, in liquid samples, only six groups were identified, namely O-H, C=C, O-H bending, C-N, C-C, and C-O. Overall, this study shows that the functional group content in fresh red ginger is higher than that in red ginger pulp, even though the temperature is lower. However, if the comparison is between the solid and liquid sample conditions for fresh red ginger with fresh red ginger or dregs with dregs, the content at a cooking temperature of 90°C is higher than 80°C. Apart from that, the higher the rock sugar content in the red ginger pulp, the higher the content of functional groups identified in the extract